2013
DOI: 10.1111/jgh.12142
|View full text |Cite
|
Sign up to set email alerts
|

l‐ornithine‐l‐aspartate for hepatic encephalopathy in patients with cirrhosis: A meta‐analysis of randomized controlled trials

Abstract: LOLA benefits both overt and minimal HE patients in the improvement of HE by reducing the serum ammonia concentration compared with the placebo/no-intervention control. Further, evaluations between LOLA and other effective treatments are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
1
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 33 publications
3
65
1
7
Order By: Relevance
“…Thus, it was concluded that hyperammonaemia may cause central fatigue. Since in most experimental studies [7,35,42,44,48] the greatest effect on ammonia reduction was achieved with L-ornithine L-aspartate (OA), it seems likely that oral intake of BCAA together with OA may reduce ammonia accumulation and cerebral absorption, thereby delaying fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was concluded that hyperammonaemia may cause central fatigue. Since in most experimental studies [7,35,42,44,48] the greatest effect on ammonia reduction was achieved with L-ornithine L-aspartate (OA), it seems likely that oral intake of BCAA together with OA may reduce ammonia accumulation and cerebral absorption, thereby delaying fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with LOLA demonstrated a significant improvement in MHE, diminished serum ammonia levels, and no increase in adverse reactions. 59 Analysis of individual studies revealed a reduction in abnormal neuropsychological testing and increased HRQoL. Further, Ndhara et al reported the effect of LOLA administration on the nutritional status of patients diagnosed with MHE.…”
Section: Lola (L-ornithine-l-aspartate)mentioning
confidence: 98%
“…Therefore, LOLA lowers plasma ammonia concentrations by enhancing metabolism of ammonia to glutamine. 59 In a meta-analysis, Bai et al evaluated 8 randomized controlled trials (total, N = 646 patients-46% diagnosed with MHE) assessing the efficacy of LOLA compared to placebo in patients with cirrhosis. Treatment with LOLA demonstrated a significant improvement in MHE, diminished serum ammonia levels, and no increase in adverse reactions.…”
Section: Lola (L-ornithine-l-aspartate)mentioning
confidence: 99%
“…The tolerance ratio, incidence of adverse events, and mortality were not significantly different between LOLA and the placebo/nointervention control. 43 However in most of the studies low grade HE (grade I-II) patients were included in whom LOLA was given in infusion form so efficacy of oral LOLA therapy still needs to be evaluated in patients with high grade HE.…”
Section: L-ornithine-l-aspartatementioning
confidence: 99%